“Too late for tears, dear sister”: Constructing victims and perpetrators of rape in the advice column ’Dear Dolly’ from 1984 to 2004. - Krige, Jana; Oostendorp, Marcelyn (Stellenbosch Papers in Linguistics Plus, 2015)
This article reports on the ways in which the rape of women by men is constructed in the advice column Dear Dolly, published in the South African periodical Drum Magazine. The data collected for the study spans from 1984 to 2004, encompassing both 10 years before and 10 years after the onset of democracy in South Africa. The article uses critical discourse analysis (Fairclough 2003) as main analytical tool, but also draws on critical feminist theory (Bourke 2007). The findings suggest that there has been a decrease in explicit victim blaming after 1994, but that subtle and opaque victim blaming is still evident in readers’ letters and in the responses. These rape discourses presented in Drum after 1994 are, as Bakhtin (1981) suggests, made up of multiple voices articulating different gendered discourses. In this article, we argue that even though the use of less explicit victim blaming might seem like a positive move in the representation of rape and gender, this is not always the case. The more subtle forms of victim blaming avoid contestation and consequently often go unchecked (Fairclough 2003: 58). Additionally, new rape myths are created to mitigate the responsibility of males. These processes of subtle victim blaming and new myth-making manufacture consent and make it more difficult to counteract dominant discourses.